Road to Strengthen of Virtual Infrastructure and Security of Remote Laboratories on Trnava University in Trnava - Beňo, Pavel; Schauer, František; Šprinková, Sandra; Šimko, Miroslav; Komenda, Tomáš (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Many organizations, both large and small, are investigating the potential of storage architectures for their companies. Few years ago, we built our own virtualized cloud for REMLABNET and we still are taking benefits of this decision. This item handels with using Cloud computing platform for providing Remote laboratories. This work shows, how it is possible to save money if we use centralized system for more consumers. Every consumer can use access to centralized portal in the Cloud computing from Consortium REMLABNET. Every item is focused on enviroments of universities, where this cloud is existing and this is what we want to use for remote labs. This is item from practice knowledge and experiences about system function and managing virtual platform and next construction this proposal.